The ayakashi hunter's tainted bride. 4 - Yuma, Midori (Kodansha USA Publishing, LLC, 2025)
"After the confrontation with Akemi and Reito, Nanao is finally able to put her traumatic past behind her and cut off ties with the Byakurenji clan. But Nanao is now having to face the heads of the Benitsubaki family--including Yako's mother, Tokiko, and his older brother, Takaya, who both seem to have a distaste for Yako and Nanao. On top of this, the ayakashi are becoming more active, and an ominous atmosphere is engulfing the capital...and what's this about Yako's former fiancee?" -- Back cover.